Differential Gene Expression Profile of Renin-Angiotensin System in the Left Atrium in Mitral Regurgitation Patients. (18th November 2018) - Liu, Wen-Hao; Fang, Yen-Nan; Wu, Chia-Chen; Chen, Mien-Cheng; Chang, Jen-Ping; Lin, Yu-Sheng; Pan, Kuo-Li; Ho, Wan-Chun; Chang, Tzu-Hao; Huang, Yao-Kuang; Fang, Chih-Yuan; Chen, Chien-Jen; et al.
Abstract : Background . Left atrial enlargement is a mortality and heart failure risk factor in primary mitral regurgitation (MR) patients. Pig models of MR have shown differential expression of genes linked to the renin-angiotensin system. Therefore, the aim of this study was to investigate the key genes of the renin-angiotensin that are expressed differentially in the left atrial myocardium in MR patients. Methods . Quantitative RT-PCR was used to compare gene expression in the renin-angiotensin system in the left atrium in MR patients, aortic valve disease patients, and normal subjects. Results . Plasma angiotensin II concentrations did not significantly differ between MR patients and aortic valve disease patients (P = 0.582 ). Compared to normal controls, however, MR patients had significantly downregulated expressions of angiotensin-converting enzyme, angiotensin I converting enzyme 2, type 1 angiotensin II receptor, glutamyl aminopeptidase, angiotensinogen, cathepsin A ( CTSA ), thimet oligopeptidase 1, neurolysin, alanyl aminopeptidase, cathepsin G, leucyl/cystinyl aminopeptidase ( LNPEP ), neprilysin, and carboxypeptidase A3 in the left atrium. The MR patients also had significantly upregulated expressions of MAS1 oncogene ( MAS1 ) and mineralocorticoid receptor compared to normal controls. Additionally, in comparison with aortic valve disease patients, MR patients had significantly downregulated CTSA and LNPEP expression and significantly upregulated MAS1 expression in the left atrium. Conclusions . Expressions of genes in the renin-angiotensin system, especially CTSA, LNPEP, and MAS1, in the left atrium in MR patients significantly differed from expressions of these genes in aortic valve disease patients and normal controls. Notably, differences in expression were independent of circulating angiotensin II levels. The results of this study provide a rationale for pharmacological therapies or posttranslational regulation therapies targeting genes expressed differentially in the renin-angiotensin system to remedy structural remodeling associated with atrial enlargement and heart failure progression in patients with MR.